VENTURY PHILANTHROPY IN BRAZILIAN STATE EDUCATIONNETWORKS: ANALYSIS OF THE INFLUENCES OF THE AYRTON SENNA INSTITUTE - Freitas Adriao, Theresa Maria de; Borghi, Raquel Fontes [UNESP] (Unesp-faculdade Ciencias & Letras, 2023)
This article is part of an inter-institutional research that mapped and analyzed basic education privatization strategies in state public education networks in Brazil. The objective is to present the Ayrton Senna Institute (IAS) incidence in the set of networks and to analyze this private actor and its modus operandi associated with philanthrocapitalism. Data on the privatization of basic education collected from the institutional pages of governments and private organizations were collected and processed. The results indicate that the IAS focused primarily on state networks in the Northeast and Midwest, elementary education, and the curricula of these networks.
Keywords: Ayrton Senna Institute; Philanthropy; Philanthrocapitalism; Privatization